2019
DOI: 10.1080/16078454.2019.1568658
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between RBC changes and coagulation parameters in high altitude population

Abstract: Objective: To explore the correlations between RBCs indexes and the basic coagulation parameters, and provide data for further studies on high altitude-induced thrombotic disease. Methods: A total of eligible 433 volunteers were divided into different groups according to HGB concentration and HCT, respectively. PT, APTT, TT and Fbg were measured by clotting assays. HGB content, HCT and PLT count were assessed by automated hematology analyzer. Results: APTT and PT were significantly higher in group 4 (high HGB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(46 reference statements)
3
11
1
Order By: Relevance
“…Our previous proteomic studies also displayed that plasma proteomics profiles significantly altered between high altitude polycythemia (HAPC) patients and HA healthy controls [14], and between HA and LA participants [15]. Moreover, we found that, in HA participants, prothrombin time (PT) and activated partial thromboplastin time (APTT) negatively correlated with hemoglobin (HGB) concentrations [26].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our previous proteomic studies also displayed that plasma proteomics profiles significantly altered between high altitude polycythemia (HAPC) patients and HA healthy controls [14], and between HA and LA participants [15]. Moreover, we found that, in HA participants, prothrombin time (PT) and activated partial thromboplastin time (APTT) negatively correlated with hemoglobin (HGB) concentrations [26].…”
Section: Introductionmentioning
confidence: 77%
“…Blood specimens were collected and prepared as we previously described [14,15,[25][26][27]. Briefly, two tubes of blood sample of each participant (∼5 mL/tube) were drawn by venipuncture.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Wu et al [10] reported that the HGB levels of normal Tibetan females ranged from 134 to 157 g/L and those of males ranged from 134 to 147 g/L, depending on the altitude. Zhang et al [11] divided WB samples of Tibetan volunteers into 4 groups according to different HGB values, which could be >184 or <166 g/L. Our team previously reported that the WB of Tibetan males had a HGB level of 165.62 g/L [12].…”
Section: Introductionmentioning
confidence: 99%
“…PLT is another factor playing a key role in thrombogenesis. Previous studies showed different effects of high-altitude exposure on PLT count ( 29 ). The result of this study is consistent with most of the other studies indicating that PLT counts were lower in plateau areas than in plain areas ( 23 , 29 31 ).…”
Section: Discussionmentioning
confidence: 99%